Alterações do hipocampo da prole de ratas tratadas com alprazolam durante a gestação - Silva, Natália Ferreira (2021)
The lack of information about the risk of using drugs during the gestational period often leads to not recommending their use in pregnant patients. However, the presence of emotional disorders is common in women in the reproductive period and their treatment during pregnancy is complex. Alprazolam is a benzodiazepine (BZD) indicated for the treatment of anxiety disorder and a commonly chosen drug for pregnant women. Additionally, alprazolam acting as a GABA agonist, finds a high density of receptors in the hippocampus. In this context, the present study aimed to study the changes in the hippocampus of the offspring of female rats treated with alprazolam during pregnancy. The rats were divided into three groups (n = 8): control (CT: 0mg / animal), treatment 1 (T1: 1.25mg / animal) and treatment 2 (T2: 30mg / animal). Alprazolam was administered orally ten days before mating and during the gestational period. After birth, newborns were counted, sexed, and the body mass of each rat pup was measured. The newborns' brains (1 animal from each mother, n = 8 per group) were extracted, 4 brains were included in paraffin and then stained using Nissl, H&E and Hoechst for hippocampus analysis; another 4 brains had the hippocampus individually macerated, and the total protein was extracted for western blotting and oxidative stress analysis. In the study, it was possible to verify that the drug affected the cell number, changed the chromatin components and the modulation of a transcriptional factor. Based on our findings, we conclude that the hippocampus consists of a plausible region of influence arising from the use of BZDs during pregnancy, however, the results do not support a relationship with the development of neurodegeneration.